Inoculation Reduces Misinformation: Experimental Evidence from Multidimensional Interventions in Brazil - Batista Pereira, Frederico; Bueno, Natália S.; Nunes, Felipe; Pavão, Nara (Journal of experimental political science, 2024)
Misinformation is widely seen as a threat to democracy that should be promptly addressed by scholars, journalists, and policymakers. However, some of the debated solutions are either controversial (internet platform regulation) or may be difficult and costly to implement in many settings (fact-checking corrections). This study investigates the effectiveness of preemptive interventions, a type of solution that has received considerably less attention in this debate. Studies show that interventions through awareness and media literacy campaigns can inoculate citizens against misinformation, but these interventions are restricted to a few contexts and settings. Our paper uses two field experiments, one of which was conducted in partnership with Brazil’s main newspaper, to investigate the effectiveness of multidimensional interventions against misinformation in São Paulo. The findings show that preemptive interventions can indeed reduce rumor acceptance and provide insights into the strategies to combat misinformation in democracies.